Perceptions and Opinions of Students Studying at Primary School Mathematics Teaching Department about the Concept of Mathematics - Altintas, Esra (Educational research and reviews, 2018)
The purpose of this study is get opinions of students on the subject of mathematics. It is thought that determining the meaning of mathematics in students' minds, the things that students associate mathematics with and the things that come to their minds when you say mathematics is vital. In this way, it is thought that it can be possible to take some precautions for enabling students to develop positive attitudes towards mathematics, making mathematics more popular among students and reducing mathematics anxiety. This study is particularly important in terms of taking the opinions of students who will be responsible for teaching mathematics and making students become more interested in mathematics so that they can take necessary precautions before they start teaching at schools. This study is a qualitative research and the data obtained through coding the answers provided by students from the Department of Teaching Primary School Mathematics. Two questions in the opinion form were divided into categories and themes were displayed in tables by given percentages and frequencies. In this sense, content analysis from qualitative data approaches and phenomenology from qualitative research designs were used. The study group consisted of 153 students (from freshman to senior) who are studying at Kafkas University, Faculty of Education, Department of Teaching Primary School Mathematics. It was concluded that students mentioned "nature," "life"," "oxygen," "everything complicated" and "puzzle" for "mathematics," and they provided answers such as "concepts related to mathematics," "middle school mathematics teacher" and "everything" for the question stated as "What is the first thing that comes to your mind when we say mathematics?"